2018
DOI: 10.3390/polym10030275
|View full text |Cite
|
Sign up to set email alerts
|

Co-Deposition of a Hydrogel/Calcium Phosphate Hybrid Layer on 3D Printed Poly(Lactic Acid) Scaffolds via Dip Coating: Towards Automated Biomaterials Fabrication

Abstract: Abstract:The article describes the surface modification of 3D printed poly(lactic acid) (PLA) scaffolds with calcium phosphate (CP)/gelatin and CP/chitosan hybrid coating layers. The presence of gelatin or chitosan significantly enhances CP co-deposition and adhesion of the mineral layer on the PLA scaffolds. The hydrogel/CP coating layers are fairly thick and the mineral is a mixture of brushite, octacalcium phosphate, and hydroxyapatite. Mineral formation is uniform throughout the printed architectures and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
(51 reference statements)
2
17
0
Order By: Relevance
“…Furthermore, the CP layer was not mechanically stable and could be dispersed. However, the presence of gelatin and or a chitosan coating on the surface significantly increased the adhesion of the CP layer onto the PLA scaffolds [146]. Prior to surface coating and mineralization, the 3D printed PLA scaffolds were hydrolyzed with NaOH to form hydroxyl and carboxyl groups on the PLA surface; then the surface was modified with 3-aminopropyltriethoxysilane (APTES).…”
Section: The Use Of Other Materials For the Surface Modification Of 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the CP layer was not mechanically stable and could be dispersed. However, the presence of gelatin and or a chitosan coating on the surface significantly increased the adhesion of the CP layer onto the PLA scaffolds [146]. Prior to surface coating and mineralization, the 3D printed PLA scaffolds were hydrolyzed with NaOH to form hydroxyl and carboxyl groups on the PLA surface; then the surface was modified with 3-aminopropyltriethoxysilane (APTES).…”
Section: The Use Of Other Materials For the Surface Modification Of 3mentioning
confidence: 99%
“…NaOH treatment cut the PLA ester bonds, producing hydroxyl and carboxylic acid groups on the surface but also caused an increase in the roughness, leading to higher contact angles than expected. The subsequent mineralization made the 3D printed scaffold biocompatible [146].…”
Section: The Use Of Other Materials For the Surface Modification Of 3mentioning
confidence: 99%
“…We have previously shown that calcium phosphate (CP), an important biomaterial [22][23][24], does not adhere to freshly printed PLA scaffolds. Consequently, the development of stable, CP-coated 3D printed PLA biomaterials is rather challenging [25][26][27]. This is unfortunate because PLA/CP composites would be prime candidates for implant materials with favorable properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogel/calcium phosphate hybrid layer [145] Significant contact angle increase Chitosan add a certain anti-infection property, gelatin is attractive for bone ingrowth Simplicity, adaptability and versatility Polydopamine/gelatin/nano HA and ponericin G1 [146] Completely hydrophilic and stronger affinity for serum…”
Section: Coating Physical Property Change Results Advantagementioning
confidence: 99%
“…[151] Nowadays, scaffold formation is typically made from materials selected by stacking struts on top of each other to achieve the final 3D object. [143,145,147,148] Many of the parameters associated with these struts and resulting meshes can vary, such as the diameter of the struts, the space between them, and the orientation from one layer to another. The macroscopic morphology of the PLA surface can even affect the orientation and morphology of the cells: the grooves of the wavy scaffold significantly induce cell elongation and change the morphology of the nucleus, whereas the cells grown on the porous scaffold are flatter and curved.…”
Section: Support For Induction Of Angiogenesismentioning
confidence: 99%